The Influence of Leadership Style and Competence of Village Apparatus on Village Government Budget Performance in Pulubala District - Adelia Abdul Talib; Mattoasi; Muzdalifah (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to analyze the influence of the leadership style and competence of village officials on the budget performance of the village government in Pulubala sub-district. The research method used was quantitative, with primary data collected through questionnaires distributed to village officials in Pulubala sub-district. The sample consisted of 121 respondents. Data analysis used multiple linear regression with the help of SPSS 26. The results of the study show that leadership style has a positive and significant influence on the performance of the village government's budget. And the competence of village apparatus also has a positive and significant influence on the performance of the village government's budget. The leadership style and competence of village officials have a significant influence on the performance of the village government's budget. The R squery value obtained was 0.579 or 57.9%, indicating a strong relationship between the independent variables and the dependent variables in this study, while the remaining 42.1% were influenced by other factors.